Delayed dosing intervals for quadrivalent human papillomavirus vaccine do not reduce antibody avidity - Allison M. Brady; Emmanuel B. Walter; Lauri E. Markowitz; Elizabeth R. Unger; Gitika Panicker (Taylor & Francis Group, 2020)
The quadrivalent HPV vaccine (4vHPV) was originally recommended as a three-dose series (0/2/6 months), though delays in completing the series frequently occur. We previously found delayed dosing in girls resulted in similar or higher antibody titers compared to on-time dosing. Archived sera from 262 healthy females aged 9-18 recruited from pediatric clinics were tested to determine if delayed dosing intervals affected antibody avidity. Avidity index (AI; ratio of IgG Ab bound in the treated and untreated sample) was determined pre- and post-dose 3 4vHPV for each participant using a modified multiplex ELISA. Data were grouped by dosing intervals: (1) on-time dose 2 and 3, (2) delayed dose 2 and on-time dose 3, (3) on-time dose 2 and delayed dose 3, (4) delayed dose 2 and 3. Overall, mean AI was highest for HPV16 and lowest for HPV6. As expected, AI did not differ between groups 1 & 3 or groups 2 & 4 pre-dose 3, however, for most types mean AI was significantly higher both pre- and post-dose 3 for groups with delayed dose 2. For all types, mean AI was higher post-dose 3 in all delayed dosing groups compared to group 1. One month post-dose 3, there was a positive but weak correlation between AIs and antibody titer for HPV 6 (ρ = 0.25, p = .0001), HPV 11 (ρ = 0.14, p = .0370), HPV 16 (ρ = 0.11, p = .0934), and HPV 18 (ρ = 0.37, p < .0001). Our findings suggest longer intervals between doses result in higher antibody avidity, providing further evidence that delayed dosing of 4vHPV does not hinder the immune response.